Model Bimbingan Kelompok Islami Teknik Truth or Dare untuk Meningkatkan Kepribadian Positif - Rusmilasari Rusmilasari; Zainal Fauz; Akhmad Rizkhi Ridhani (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2020)
The objectives of this research are: (1) knowing the procedure for developing service models, (2) knowing the service model according to academics and practitioners. This study uses a research and development (R&D) method, with the following steps: (1) preliminary study. (2) development of a hypothetical model. (3) expert validation. (4) model revision. Based on the validation of Academic experts and Practitioners, it can be seen that the results of the validation of the material Academics got a score of 29.5 or very good and the results of Practitioner validation with a score of 22.2 or good and the result of a service model. Conclusion: The positive personality of students before being given service is in the low category and after being given the service it is in the high category. Keywords: Group Guidance Islamic, Truth or Dare Technique, Positive Personality